Character Building: Strategies to Build ‎Student's Moderate Attitudes in Madrasah ‎Culture‎ - Hilyah Ashoumi; M Kris Yuan Hidayatulloh; Dwiky Maulana Ashari (TADRIS: Jurnal Pendidikan Islam, 2023)
The purpose of this study is to describe and analyze the formation of moderate attitudes through madrasah culture at MA Unggulan KH. Abd. Wahab Hasbulloh (MAUWH) Tambakberas. This research focuses on the strategy of building moderate attitudes of students and its implications at MAUWH. This research uses qualitative methods. Data collection techniques are done through interviews, observation, and documentation. Data analysis techniques through three paths; namely data condensation, data presentation, and conclusion drawing. The results of this study found that the strategy of building moderate attitudes of students at MAUWH through the creation of a religious atmosphere, internalization of values, habituation and exemplary. The strategy is recorded in the character-building program which is applied to activities such; praying dhuha and praying dhuhur in the congregation, istighasah, sapa tetangga, Bhakti BU, and Inspiring. The implication of these strategic activities is the emergence of attitudes that are accustomed to worshiping, respecting others, having social care, and being tolerant which is an indicator of a moderate attitude.